One sample—three new species: an example of species richness of the genus Symplecis Förster, 1869 (Hymenoptera, Ichneumonidae: Orthocentrinae) in Burundi - Varga, Oleksandr (Zootaxa, 2023)
Three new orthocentrine species of the genus Symplecis Förster, 1869 are described and illustrated: S. aperta sp. n., S. glabroscutum sp. n. and S. kibiraensis sp. n. These species were all found in one sample collected by Malaise trap in Kibira National Park (Burundi) demonstrating potentially high species richness of the genus in the Afrotropics compared with other regions.